The In-Vitro Digestibility of Dry Matter and Organic Matter of Banana Stem Combined With Kembang Telang (Clitoria ternatea) Silage - O., Dewi; Suryani, N. N.; Mudita, I M. (Jurnal Peternakan Tropika; Vol 8 No 1 (2020): Issue 8 No. 1 (2020); January - April, 2020)
Banana stems have the potential as a source of feed because of its high rate of production, but it is easily spoiled due to it containing high level of water content. Because of this, it is necessary to use alternatives process such as silage. The purpose of this study is to identify the adequate level of Clitoria ternatea addition into banana stem silage that was measured through in vitro digestibility. The silage was created at the Universitas Udayana Faculty of Husbandry’s Sesetan Farm, which is at Sesetan Street , Substreet of Markisa , Denpasar, for 4 weeks. The in-vitro digestibility analysis was conducted at the Universitas Udayana Faculty of Husbandry’s Nutrition and Animal Feed Laboratory for 12 weeks. Completely Randomized Design (CRD) was used in this experiment with 4 treatments and 4 replicates. The treatment consists of A (65% banana stem + 30% pollard + 5% (mollases+EM4)), B (55% banana stem + 10% C. ternatea + 30% pollard + 5% (mollases+EM4)), C (45% banana stem + 20% C. ternatea + 30% pollard + 5% (mollases+EM4)), and D (35% banana stem + 30% C. ternatea + 30% pollard + 5% (mollases+EM4)). The variables measured were the dry matter digestibility, organic matter digestibility, nitrogen free extract/NFE, and total digestible nutrients/TDN. The results showed that the dry matter and organic matter digestibility percentage increase has a significantly (P<0.05) and treatment D shows the highest increase for dry matter and organic matter digestibility of 70.40% and 73.08%, respectively. Nitrogen free extracts and total digestible nutrients showed that no significantly (P>0.05), but quantitatively increases with treatment D having the highest rate of nitrogen free extracts and total of digestible nutrients of 38.39% and 78.58%, respectively. The concluded of this study showed that the highest rate of dry matter and organic matter digestibility increased by adding 20% of Clitoria ternatea. Keywords: Banana stem, Clitoria ternates, In-vitro Digestibility, Silage